A “Misfit” Theory of Spontaneous Conscious Odor Perception (MITSCOP): reflections on the role and function of odor memory in everyday life - Köster, Egon P.; Møller, Per; Mojet, Jos (Frontiers in Psychology, 2014)
Our senses have developed as an answer to the world we live in (Gibson, 1966) and so have the forms of memory that accompany them. All senses serve different purposes and do so in different ways. In vision, where orientation and object recognition are important, memory is strongly linked to identification. In olfaction, the guardian of vital functions such as breathing and food ingestion, perhaps the most important (and least noticed and researched) role of odor memory is to help us not to notice the well-known odors or flavors in our everyday surroundings, but to react immediately to the unexpected ones. At the same time it provides us with a feeling of safety when our expectancies are met. All this happens without any smelling intention or conscious knowledge of our expectations. Identification by odor naming is not involved in this and people are notoriously bad at it. Odors are usually best identified via the episodic memory of the situation in which they once occurred. Spontaneous conscious odor perception normally only occurs in situations where attention is demanded, either because the inhaled air or the food smell is particularly good or particularly bad and people search for its source or because people want to actively enjoy the healthiness and pleasantness of their surroundings or food. Odor memory is concerned with novelty detection rather than with recollection of odors. In this paper, these points are illustrated with experimental results and their consequences for doing ecologically valid odor memory research are drawn. Furthermore, suggestions for ecologically valid research on everyday odor memory and some illustrative examples are given.